2013
DOI: 10.1111/asj.12142
|View full text |Cite
|
Sign up to set email alerts
|

Actions of intravenous injections of AVP and oxytocin on plasma ACTH, GH, insulin and glucagon concentrations in goats

Abstract: This study was conducted to investigate the arginine-vasopressin (AVP)- and oxytocin-induced changes in plasma adrenocorticotropic hormone (ACTH), growth hormone (GH), insulin and glucagon levels and their metabolite concentrations in goats. In this study, five goats were intravenously injected with either AVP (0.3 nmol/kg body weight (BW)) or oxytocin (0.7 IU/kg BW). AVP injection significantly increased ACTH and GH secretions compared to controls, although insulin and glucagon concentrations were not altered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
(91 reference statements)
0
5
0
Order By: Relevance
“…Levels of β‐hydroxybutyrate (BHBA) were determined via UV and colorimetric methods using F‐kits (R‐Biopharm AG, Darmstadt, Germany). Concentrations of GH, insulin, and IGF‐1 were analyzed according to the methods of our previously published studies (Roh et al., ; Suzuki et al., ). The detection limits of growth hormone (GH), insulin, and insulin‐like growth factor 1 (IGF‐I) were 0.03 ng, 0.031 ng, and 1.86 pg in tube, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Levels of β‐hydroxybutyrate (BHBA) were determined via UV and colorimetric methods using F‐kits (R‐Biopharm AG, Darmstadt, Germany). Concentrations of GH, insulin, and IGF‐1 were analyzed according to the methods of our previously published studies (Roh et al., ; Suzuki et al., ). The detection limits of growth hormone (GH), insulin, and insulin‐like growth factor 1 (IGF‐I) were 0.03 ng, 0.031 ng, and 1.86 pg in tube, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Intranasal application in dogs increases glucagon and insulin secretion (37), and this is probably mediated peripherally as intravenous oxytocin has a similar effect in goats (38) and dogs (39). In rats, oxytocin receptors are expressed by glucagon-and insulin-secreting cells in the pancreas (40), and direct stimulation of glucagon release has been characterised in vitro (41).…”
Section: Peripheral Targets For Oxytocinmentioning
confidence: 99%
“…3 Animal studies have shown that direct injection of oxytocin centrally suppressed the desire for food consumption and influenced glucose metabolism. [4][5][6] Knock-out OXT-or OXTR-gene mice developed hyperphagia and obesity phenotypes. 7,8 In addition, a feedback of oxytocin secretion can be stimulated by changes in glucose metabolism.…”
Section: Introductionmentioning
confidence: 99%